Activating lone parents: an evidence-based policy appraisal of the recent welfare-to-work reform in Britain - Haux, Tina (Colchester, 2010)
"The recent welfare-to-work reform requires lone parents with older children to be available for work. This article examines the likely effect of this reform and the proposed extension with regards to the employment rate of lone parents. It is argued that it will not lead to the desired increase in the employment rate of lone parents as the target group is too small and the levels of multiple disadvantages within the group too high. Indeed, 'ability to work' cannot be equated with the age of the youngest child but needs to take into account the characteristics of lone parents as well."